An octapeptide analogue of HIV gp120 modulates protein tyrosine kinase activity in activated peripheral blood T lymphocytes. - Phipps, D J (1995)
Following infection with HIV, patients exhibit lymphocyte dysfunction before the loss of CD4+ T cells. The major HIV surface glycoprotein, gp120, can modulate lymphocyte function in vitro; however, the mechanism by which gp120 affects T lymphocyte signal transduction is controversial. We have used Peptide T, a synthetic octapeptide derived from a conserved, CD4 binding region of gp120, to examine gp120-related modulation of lymphocyte signal transduction. Activation of lymphocytes through the T cell receptor (TCR) in collaboration with cell surface accessory molecules results in rapid increases in tyrosine phosphorylation, probably through the recruitment and activation of src-family protein tyrosine kinases (PTK) such as lck and fyn which have been implicated in mediating the proximal signalling events mediated through the TCR. To identify potential mechanisms by which gp120 could modulate the function of T lymphocytes, we determined the effect of Peptide T on normal, activated peripheral blood lymphoblasts. Treatment of normal, activated peripheral blood lymphoblasts with Peptide T (10(-9) M) for 60 min transiently reduced levels of protein tyrosine phosphorylation (ptyr). Reduction in levels of cellular ptyr was associated with transient inhibition of the activity of total cellular and CD4-associated p56lck kinase activity (80%). Peptide T also induced a small delayed reduction in the p59fyn activity (up to 42%). Despite the decrease in total cellular ptyr levels, pp60c-src kinase activity was increased 11-fold following treatment with Peptide T. Peptide T pretreatment also induced tyrosine phosphorylation of a 48-kD CD4-associated protein, indicating that Peptide T may have multiple effects. Peptide T did not alter the levels of total cellular p56lck enzyme, nor did it directly inhibit the activity of purified p56lck. These results are consistent with a Peptide T-dependent modulation of PTK regulation, and support the potential of gp120 to interfere with T lymphocyte signal transduction in activated T lymphocytes.